End-of-life vehicle recovery factors: Malaysian stakeholders' views and future research needs - Mohamad-Ali, Nurhasyimah; Ghazilla, Raja Ariffin Raja; Abdul-Rashid, Salwa Hanim; Sakundarini, Novita; Ahmad-Yazid, Aznijar; Stephenie, Lydyaty (Wiley, 2018)
In this study, we identify the factors that affect end-of-life vehicle (ELV) recovery effectiveness in order to develop an improved ELV recovery model in Malaysia. We derived these factors from a literature survey and on-site interviews with representatives of selected local companies who are the key stakeholders in ELV management. We used the system dynamics approach to identify the link between the ELV recovery factors and recovery effectiveness, and we present the results in the form of an aftermarket cognitive map, which provides a pictorial view of the interrelationships between the ELV recovery factors. Indeed, we found that the factors conform well with those identified in previous studies. We believe that the improved ELV recovery model will be beneficial to product designers and stakeholders in the ELV recovery network, and encourage them to take action in accordance with the National Automotive Policy in line with the ELV directive.